Phytochemical investigation, antibacterial and antioxidant activities of Sideritis incana L extracts - Sefaoui, Asma Khelassi; Zaoui, Manel; Daouadji, Djelloul; mekhelfi, Tarak; Nailic, Imane; Zaiter, Lahcen; Benarima, Hanane; Khechekhouche, Abderrahmane (جامعة الوادي - university of el oued, 2021)
According to the phytochemical investigation conducted on the Sideritis incana L. plant, it was found to be rich in secondary metabolites, in particular tannins, flavonoids and alkaloids, based on what we found by preliminary tests for chemical constituents. The content of phenols, flavonoids was estimated by spectrophotometric methods. Also, the antioxidant activities of the extracts of Sideritis incana L were investigated by DPPH scavenging, and phosphomolybdenum method. The results of the quantitative estimation of total phenols showed the highest content in chloroform where it was estimated 585.64 mg GAE /g followed by n-butanol 282.22 mg GAE /g and the lowest content recorded in petroleum ether 17.32 mg GAE /g. The results of the quantitative evaluation of flavonoids showed that petroleum ether fraction contained an excess of flavonoids in the unusual results. For the DPPH assay, n-butanol fraction showed the best result followed by the ethyl acetate fraction and finally chloroform fraction the lowest activities ( IC50 = 0.0534, 0.071 and 0.0756 μg/ml) respectively. Finally, result of antibacterial activity of S.incana showed that the chloroform extract gave the highest diameter inhibition among all extracts (13 mm) at a concentration of 50 mg/ml against Escherichia coli ATCC25921 and Staphylococcus aureus ATCC25923
Article
Keywords: Sideritis incana L; Antioxidant activity; Antibacterial activity; Phenolic content; Alkaloids